Structural and functional abnormalities of large arteries in the Turner syndrome - Baguet, J-P; Douchin, S; Pierre, H; Rossignol, A-M; Bost, M; Mallion, J-M (Heart (British Cardiac Society), 2005)
Objective: To analyse the structural and functional abnormalities in the large arteries in women with the Turner syndrome. Methods: Aortic stiffness (assessed by means of the carotid femoral pulse wave velocity), level of amplification of the carotid pressure wave (by applanation tonometry), and carotid remodelling (by high resolution ultrasound) were studied in women with the Turner syndrome. Clinical and ambulatory blood pressures were taken into account in the analysis. Thus, 24 patients with the Turner syndrome and 25 healthy female subjects matched for age were studied. Results: Women with the Turner syndrome had a higher augmentation index than the controls (Turner, mean (SD) 0.04 (0.14) v controls, −0.14 (0.13), p < 0.001) but a lower peripheral pulse pressure (39 (8) mm Hg v 47 (11) mm Hg, p  =  0.010 in the clinic; 44 (5) mm Hg v 47 (6) mm Hg, p  =  0.036 during the 24 hour ambulatory recording). The luminal diameter of the common carotid artery and the carotid–femoral pulse wave velocity were similar in the two groups, whereas carotid intima–media thickness tended to be higher in women with the Turner syndrome (0.53 (0.06) mm v 0.50 (0.05) mm, p  =  0.06). After correction for body surface area, carotid intima–media thickness and pulse wave velocity were higher in women with the Turner syndrome. Conclusions: Vascular abnormalities observed in the Turner syndrome are implicated in the origin of the cardiovascular complications that occur in this syndrome. These abnormalities are morphological but also functional. An increase in the augmentation index can be explained in part by the short height of these patients.